HUBUNGAN KADAR 25-HYDROXYVITAMIN D SERUM DENGAN TEKANAN DARAH MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS BAITURRAHMAH - Habibi Akbar; Jelmila, Sri Nani; Aryaldi Zulkarnaini; Roland Helmizar (Yayasan Nusantara Hasana Berdikari, 2024)
Serum 25 hydroxyvitamin D levels are an indicator of the body's vitamin D status. Vitamin D is physiologically involved in regulating blood pressure by regulating the Renin Angiotensin Aldosterone system. Students are a group of young adult individuals who are at risk of being exposed to less sunlight, which means their 25-hydroxyvitamin D levels are insufficient. Research objectives: This study aims to determine the relationship between serum 25-hydroxyvitamin D levels and blood pressure in students at the Faculty of Medicine, Baiturrahmah University. This research used an observational analytical method with a cross sectional design. The sample for this research was 58 students from the Faculty of Medicine, Baiturrahmah University, Padang, class 2020-2023. The largest gender was female, namely 42 people (72.4%), the highest age was 20 years (44.8%), the average 25-hydroxyvitamin D level was 24.49 ng/ml, the average systolic blood pressure was 119.14 mmHg, and the average diastolic blood pressure was 79.64 mmHg. The results of the Spearman correlation analysis of serum 25 hydroxyvitamin D levels with systolic blood pressure obtained values ​​of r=0.22 and p=0.09, correlation analysis of serum 25 hydroxyvitamin D levels with diastolic blood pressure obtained values ​​of r=0.03 and p=0, 79. There is no relationship between serum 25 hydroxyvitamin D levels and systolic and diastolic blood pressure of students at the Faculty of Medicine, Baiturrahmah University.